TestAXE: Automatically Refactoring Test Smells Using JUnit 5 Features - Paula, Estevan Alexander de; Bonifácio, Rodrigo (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2022)
Test smells have been proven to deteriorate the quality of the test suite of a system, to the point where several different tools have been devised with the objective of detecting or sometimes even fixing these smells. Have been extensively studied in more recent years, these smells have been cataloged and researchers have proposed a series of source code transformations capable of eliminating these smells. Our goal in this paper is to present TESTAXE, a tool to refactor test smells using the latest features of JUnit 5. We present an empirical assessment of TESTAXE accuracy and highlight its current limitations.